Local congestion control algorithm with fair channel allocation - Geng-ming ZHU; Zhi-qiang WANG; Zhe-tao LI; Ren-fa LI (Tongxin xuebao)
A local congestion control algorithm with fair channel allocation (FCA) was presented to mitigate local congestion as well as to improve the fairness of channel utilization.In order to decrease the extra communication overhead for obtaining the real-time buffer length of neighbors and improve the accuracy of congestion detection model based on buffer occupancy of single node，FCA presented a new model considers the total buffer length of neighbors with predict-based mechanism for real-time buffer occupancy and the average transmission time of packet.To avoid deteriorating congestion with an explicit notified package，FCA embedded an additional node address to the ACK control frame to carry congestion information.During the congestion alleviation stage，FCA presented a fair channel allocation mechanism based on real-time buffer occupancy and queue priority to prevent some nodes from overflowing resulting in package loss due to the growth of buffer fast.Simulation results show that the proposed protocol has comparative advantages compare with 802.11，CODA and PCCP in terms of collision，package delivery ratio，throughput and fairness.